KEBIJAKAN PENGENDALIAN TEMBAKAU TERHADAP EKSISTENSI INDUSTRI TEMBAAU DI JEMBER (1999-2015) - Cristi Antika MuliawatI; Sri Ana Handayani (Fakultas Ilmu Budaya Universitas Jember, 2017)
AbstractThis article explained about the birth of historical-background of tobacco controlling policy and the effect for Jember society. Then, the policy influenced the response from Jember goverment and tobacco society in Jember. The method of this research used historical method including research manners and historical writings. Tobacco controlling policy was backed by the interest of foreign capitalist that threaten Jember economic society who their life was depend on tobacco for instances farmers, tobacco sellers, cigarette sellers, etc. Those problems influenced the reaction from Tobacco farmer Association of Indonesia (APTI) in Jember and tobacco society. APTI Jember prosecuted Jember government to protect the farmers that threathen because of tobacco controlling policy. Besides, The response was also given by the small businessman cigarette in Jember. The cigarette businessman in Jember did against by producing the cigarette without any tax as a way to oppose the policy of tax that was very high at that time. Jember goverment was very responsive to face the problem that made tobacco society worried about the tobacco policy. Then, the government did a cooperation with tobacco society to conserve tobacco. One of the ways to consrve tobacco was by running tobacco affair policy and by using DBHCHT that agreed with tobacco society requirement. The response that was given by tobacco society and Jember government could not be seperated from the importance of tobacco for the economy of Jember society.